On The Time-Interval Problem - Rocha, Fábio Rodrigues de la (Anais do Workshop de Sistemas Operacionais (WSO), 2008)
In this paper we present a modeling technique to capture the actual interference among segments in the time-interval problem. Also, we explore the subject of fixed priority assignment for segments through both optimal and suboptimal algorithms. As a result, we develop a less pessimistic offline feasibility test which results in higher QoS values comparing to previous studies.